Lignans from Euphorbia hirta L. Issue 1 (22nd December 2021) - Zhang, Ling; Wang, Xiao-Ling; Wang, Bin; Zhang, Long-Teng; Gao, Hui-Min; Shen, Tao; Lou, Hong-Xiang; Ren, Dong-Mei; Wang, Xiao-Ning
Abstract: Five new lignans, euphorhirtins A–D (1 –4 ), 5-methoxyvirgatusin (5 ), three artefacts, 7 S -ethoxyisolintetralin (6 ), 7 R -ethoxyisolintetralin (7 ), and 7 R -ethoxy-3-methoxyisolintetralin (8 ), together with 13 known ones (9 –21 ) were isolated from the medicinal plant Euphorbia hirta L. The structures of the compounds were elucidated by means of extensive spectroscopic analysis, including 1D and 2D NMR and HR-ESI-MS experiments. The absolute configurations of compound 1 was determined by ECD calculation. The isolates were evaluated for their inhibitory effects against the proliferation of the cancer cell lines (Hep G2, A549, and DU145) and compounds 14 and 18 showed inhibitory activity against the Hep G2 cells with IC50 values 7.2 ± 0.17 and 8.5 ± 0.36  μ M. Graphical Abstract: